Woody plants diversity and its relationship with carbon stock in the tropical moist evergreen closed forest, Dong Nai Cultural Nature Reserve - Thi Luong, Nguyen; Van Quy, Nguyen; Van Hop, Nguyen (Journal of Forestry Science and Technology, 2023)
This study was conducted to test the hypothesis of a statistically meaningful existence between woody plant diversity and aboveground carbon stock in the tropical moist evergreen closed forests at Dong Nai Cultural Nature Reserve. The result showed that, in total, 49 plant species of 30 families were recorded. Twenty-one threatened species were listed in Decree 84/2021/ND-CP of the Government, Vietnam Red Data Book (2007), and IUCN Red List (2022). The indicators reflecting the level of diversity were identified: Species richness (S) 15.44±2.69 species; Abundance (A) 51.68±3.42 trees; Margalef (d) 3.66±0.69; Pielou (J’) 0.87±0.05; Simpson (Cd) 0.13±0.04; and Shannon-Wiener (H’) index 2.36±0.25. The ability to carbon stock aboveground ranged from 78.67 tons/ha to 255.64 tons/ha, with an average of 161.04±54.38 tons/ha. Furthermore, the linear correlation between species richness (S), tree abundance (A), Margalef index (d), Pielou (J’), Simpson (Cd), and aboveground carbon was not found. Meanwhile, a statistically significant but very weak correlation between Shannon-Wiener (H’) and aboveground carbon was detected. Thus, the original hypothesis was that woody plant diversity and aboveground carbon did not occur. Therefore, priority should be given to managing and conserving plant diversity instead of promoting the study area’s aboveground biomass and carbon accumulation function.